Participatory Integrated Climate Services for Agriculture (PICSA): Planning and Review Meetings for Kondoa and Kiteto Districts, Tanzania - Gathenya, John (2017)
A one-day planning and review meeting took place on December 14th 2016 for the Kondoa District and on December 15th for the Kiteto District. Participatory Integrated Climate Services for Agriculture (PICSA) training aims to build the capacity of end users of climate services in the agriculture and food security sectors to enable them make better decisions and become more resilient to risks arising from climate variability. This meeting was a follow up to the PICSA intermediary training that was held in September and October 2016, after which the intermediary or extension workers returned to their villages to implement PICSA. This planning and review meeting evaluated the success of PICSA implementation and attempted to tackle the challenges that extension workers faced by revising the difficult areas of the PICSA manual and making recommendations that can be taken up by decision makers and hence make PICSA more sustainable. The experiences of the extensions workers demonstrate that PICSA can be integrated in the package of support to farmers and pastoralists.